Tra media e moda. La comunicazione di moda nella platform society - Mauro Ferraresi (Ocula, 2023)
This contribution aims to investigate the relationship between fashion and media in today's digital age. It analyses the main effects of this pairing, which, under the name of fashion-media, investigates the relationship between fashion and media consumption, analyses elements of the fashion industry in the light of the platform society and, finally, outlines some of the consequences of fashion-media.